2011
DOI: 10.1051/0004-6361/200913498
|View full text |Cite
|
Sign up to set email alerts
|

On the evolution of environmental and mass properties of strong lens galaxies in COSMOS

Abstract: Context. Nearly 100 new strong-lens candidates have been discovered in the COSMOS field. Among these, 20 lens candidates with 0.34 z lens 1.13 feature multiple images of background sources. Aims. Using the multi-wavelength coverage of the field and its spectroscopic follow-up, we characterize the evolution with redshift of the environment and of the dark-matter (DM) fraction of the lens galaxies. Methods. We present spectroscopic and new photometric redshifts of the strong-lens candidates. The lens environment… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
59
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(64 citation statements)
references
References 65 publications
5
59
0
Order By: Relevance
“…Previous studies have only shown weak evolution of the dark matter fraction with redshift (Treu & Koopmans 2004;Auger et al 2010;Faure et al 2011;Ruff et al 2011), in agreement (within the errors) with our findings. However, the mass resolution attainable with the current information does not permit significant constraints on the evolution, with no evolution also being consistent within the uncertainties.…”
Section: Summary and Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Previous studies have only shown weak evolution of the dark matter fraction with redshift (Treu & Koopmans 2004;Auger et al 2010;Faure et al 2011;Ruff et al 2011), in agreement (within the errors) with our findings. However, the mass resolution attainable with the current information does not permit significant constraints on the evolution, with no evolution also being consistent within the uncertainties.…”
Section: Summary and Discussionsupporting
confidence: 93%
“…In particular, strong lensing systems in which both lenses and sources are galaxies can provide insights into several current astrophysical and cosmological topics. For example, the configuration of the lensing-induced multiple images and arcs of a background source and their relative fluxes can be used to study the mass profile of lensing galaxies (e.g., Kochanek & Dalal 2004;Gavazzi et al 2007) and their evolution (e.g., Faure et al 2011;Lagattuta et al 2010;Treu et al 2005), including the measure of galactic substructure (e.g., Vegetti & Koopmans 2009;Keeton & Moustakas 2009). On the other hand, the magnification induced by lensing allows for the study of intrinsically faint and distant sources (e.g., Claeskens et al 2006;Anguita et al 2009;Koester et al 2010;Bayliss et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The comparatively less massive S4TM lens sample serves as a complementary addition to the current galaxy-scale strong-lens samples, which are usually biased toward more massive lens galaxies (e.g., Auger et al 2010;Faure et al 2011;Brownstein et al 2012;Sonnenfeld et al 2013). It extends the lens-galaxy mass coverage to the lower-mass end, and can allow a more thorough investigation of the mass structure and scaling relations of ETGs when combined with other strong-lens samples, especially the SLACS sample which is selected from the same parent sample with the same selection technique.…”
Section: Discussionmentioning
confidence: 99%
“…In some cases the datasets are restricted to small samples and small redshift windows to evaluate the dependence of the galaxy DM content on redshift, as in the case of gravitational lenses (Auger et al 2009, 2010, Tortora et al 2010bSonnenfeld et al 2013). The first studies have given contrasting results (Faure et al 2011;Ruff et al 2011). The reason of the tensions among these latter studies probably resides in the paucity of the galaxy samples and differences in the model choices.…”
Section: Introductionmentioning
confidence: 99%